2012
DOI: 10.1371/journal.pone.0032364
|View full text |Cite
|
Sign up to set email alerts
|

SP7 Inhibits Osteoblast Differentiation at a Late Stage in Mice

Abstract: RUNX2 and SP7 are essential transcription factors for osteoblast differentiation at an early stage. Although RUNX2 inhibits osteoblast differentiation at a late stage, the function of SP7 at the late stage of osteoblast differentiation is not fully elucidated. Thus, we pursued the function of SP7 in osteoblast differentiation. RUNX2 induced Sp7 expression in Runx2 −/− calvarial cells. Adenoviral transfer of sh-Sp7 into primary osteoblasts reduced the expression of Alpl, Col1a1, and Bglap2 and mineralization, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 37 publications
5
72
1
2
Order By: Relevance
“…Consequently, it is likely that suppression of osterix is associated with a reduction in postnatal development in mutant mice. By contrast, it was recently suggested that osterix and Runx2 inhibit osteoblast differentiation at a late stage in an independent manner of Runx2 and osterix, respectively, where osterix positively regulates its own promoter (Yoshida et al, 2012). In this study, we showed that unlike Runx2, the mRNA expression of osterix in mutant mice was quite dynamic and thus its level was higher in the mutant than control mice at 2 weeks of age.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Consequently, it is likely that suppression of osterix is associated with a reduction in postnatal development in mutant mice. By contrast, it was recently suggested that osterix and Runx2 inhibit osteoblast differentiation at a late stage in an independent manner of Runx2 and osterix, respectively, where osterix positively regulates its own promoter (Yoshida et al, 2012). In this study, we showed that unlike Runx2, the mRNA expression of osterix in mutant mice was quite dynamic and thus its level was higher in the mutant than control mice at 2 weeks of age.…”
Section: Discussioncontrasting
confidence: 63%
“…Ihh expression was also found to up-regulate the function of Runx2 through Gli2 (Shimoyama et al, 2007). In addition, ectopic Ihh expression in chondrocytes mediates Runx2 induction throughout the perichondrium, although Ihh alone is not sufficient to induce bone formation (Komori, 2012). Moreover, sonic hedgehog (Shh) is the most widely characterized of three analogous proteins in mammals and is essential for proper development in both embryonic and adult stages.…”
Section: Introductionmentioning
confidence: 99%
“…Runx2 and Osterix encode essential transcription factors for osteoblast commitment and differentiation at an early stage (Kanatani et al, 2006;Komori et al, 1997;Liu et al, 2001;Nakashima et al, 2002). Recently, Yoshida et al reported that sustained expression of Osterix and Runx2 inhibited osteoblast differentiation from proceeding to a late stage in a reciprocally independent manner (Yoshida et al, 2012). Therefore, it is possible that the inverse temporal downregulation and upregulation of transcription factors such as Runx2 and Osterix, as was observed in vitro (Fig.…”
Section: The Roles Of the Cx3cr1-cx3cl1 Axis In Osteoblast Differentimentioning
confidence: 84%
“…The expression of Osx begins at around day E13.5 and it promotes the expression of osteoblast markers such as Alpl, Ibsp, and Bglap. The expression of Osx has been shown to be positively regulated by BMP, insulin-like growth factor 1 (IGF1), and MAPK signaling pathways in undifferentiated MSCs , Ortuno et al 2010, and it can also regulate its own expression by interacting with its own promoter (Yoshida et al 2012).…”
Section: Mirnas and Osteoblast Differentiationmentioning
confidence: 99%